Tradisi Ngopur Tontonan Dan Temunih Masyarakat Madura Sungai Pinyuh Mempawah Kalimantan Barat - Misdi, Misdi; Arkanudin, Arkanudin; Batuallo, Ignasia Debbey (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research is motivated by the activities of the Madurese community in Sungai Pinyuh Mempawah in treating the newborn baby's placenta by burying it with special treatment equipped with certain objects in its implementation, by the Madurese community called the tradition of ngopur tontonan and temunih. The purpose of the research is to explain the history of the ngopur tontonan and temunih traditions, the implementation process and the meaning contained in the ngopur tontonan and temunih traditions. The study is descriptive and qualitative with an ethnographic approach, using data collection techniques of observation, interviews, and documentary research related to the research question. Data analysis techniques use interactive analysis that begins with collecting, reducing, presenting, and drawing conclusions from data. The results and conclusions of the research show that the tradition of ngopur tontonan and temunih is still maintained because the tradition is a legacy of ancestors who were brought from Madura Island, Sumenep Regency, East Java to West Kalimantan. This tradition is still carried out because the Madurese community has a belief that the umbilical cord, placenta or spectacle of a newborn baby is considered a twin brother and companion of his children, even though the baby is physically separated by the umbilical cord. Therefore, the umbilical cord requires special care, such as being washed thoroughly, wrapped in white cloth, given various paraphernalia and burial. This is a sign of respect which means that it should not be treated normally, it must be done in a special way before being buried into the ground. The equipment used in the tradition of ngopur tontonan and temunih is a symbol of the prayers and hopes of parents for their children, so that these prayers help children in facing various problems when a child grows up will face many unpredictable problems.